Proceedings of the International Conference on Current Problems in Engineering and Applied Sciences (ICCPEAS 2025) - Rovnag Rzayev; Tural Naghiyev; Rena Babayeva; Amdulla Mekhrabov; Turan Mammadova (Atlantis Press International BV, 2026)
This open access volume presents select peer-reviewed papers presented at the International Conference on Current Problems in Engineering and Applied Sciences (ICCPEAS 2025).